Recognizing Synrift and Postrift Structures on Rock Exposures in The Tanjung Aur II Region, South Bengkulu, Indonesia - Rio Hanzra Adjie Pamungkas; Edy Sutriyono (UIR PRESS, 2024)
Field observation has been carried out recently in the Tanjung Aur II region, South Bengkulu in order to recognize the structural configuration of rock sequences, employing two fundamental approaches such as the analysis of Digital Elevation Model (DEM) and the surface mapping, particularly on geological structures. The DEM analysis reveals two general patterns of the NE-SW and NW-SE lineaments. The NE-SW trend appears consistent with the structural features resulted from the WNW-directed rifting event, whereas the NW-SE orientation seems coincident with the general strike of the Bengkulu Basin. The field mapping has recognized five types of brittle structures and two ductile deformations. The outcropping brittle deformation includes the Tanjung Aur II-A listric extensional fault, Tanjung Aur II-B listric extensional fault, Tanjung Aur II-C domino extensional fault, and Tanjung Aur II-D listric extensional fault that all strike to NE-SW, and the Air Selali compressional fault which trends to NW-SE. The recognized ductile structures are those of the Air Kenidian Anticline and Syncline, which have a general trend to NW-SE. Importantly, the encountered structures suggest two distinct episodes of tectonic events, transtension and transpression. The transtensional regime associated with the WNW extension of rifting. The synrift event commenced in Paleogene or Paleocene-Eocene time, and proceeded up to Neogene. Hence, the sedimentary influx within the basin had likely been accommodated by the occurring tectonic deformation which resulted in the synrift listric extensional faults. The transpressional regime in the study area led to ductile deformation responsible for thrusting and folding of sedimentary sequences. This post-rifting episode perhaps associated with the onset of Barisan orogeny that allowed inversion of sedimentary basin in Late Neogene or Plio-Pleistocene time. Herein, this tectonic episode is considered as the last event that caused the rock successions to be uplifted and the generated structures in rock units to be exposed at the surface due mainly to denudation and erosion.